Politik Luar Negeri Indonesia: Pantulan dari 'Weak State' dan Masa Transisi yang Berkepanjangan - Djafar, Zainuddin (Global: Jurnal Politik Internasional, 2004)
Evaluation of Indonesian foreign policy leads us to assess the following: Firstly, since the Soeharto era we have had close relations with the Western countries, we have enjoyed billions of US dollars of loans, held technical co-operations in various aspects, we have oil reserves, LNG and other potential natural sources; but as a result of the multidimensional crises in 1997-1999, our economic and business activities, as well as financial and banking systems, have been ruined. Secondly, the three following administrations (B.J. Habibie, Abdurrahman Wahid and Megawati Soekarnoputri, 1998-2004) were not able to do much, let alone restore Indonesia to its former position as a respected country among ASEAN community. Thus, Indonesia has continued to deal mainly with its problems of internal crises and undeniably, has become increasingly dependent of the mercy of Western countries (including the donor agencies and international financial institutions) regarding financial loans and other economic aids. This article is aimed to explain: (a) the meaning of the term “weak state” (b) what can Indonesia do with its foreign policy, which inevitably has to compromise with the “Weak State” condition? (c) what are the policies that should be implemented so that we can come out of the delicate situation?